2021
DOI: 10.1002/pam.22282
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Special Education on the Academic Performance of Students with Learning Disabilities

Abstract: In the 40‐plus years since the Individuals with Disabilities Education Act, special education has grown in the number of students and amount spent on services. Despite this growth, academic performance of students with disabilities remains troublingly low compared to general education students. To some extent, these differences reflect persistent underlying disabilities, but they also may reflect ineffective services. Does special education improve academic outcomes for students with disabilities? There is sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 22 publications
(23 reference statements)
2
32
0
1
Order By: Relevance
“…Students who receive counseling seem to fare better academically in comparison to those who do not receive any intervention but who exhibit similar difficulties and characteristics. This effect is four times the 0.1 standard deviation effect size criterion for successful interventions suggested by Bloom et al (2006) and Schwartz, Hopkins, and Stiefel (2021). Academic support offers no benefits but does not harm either.…”
Section: Returns To Special Education Programs In Inclusive School Se...mentioning
confidence: 59%
See 2 more Smart Citations
“…Students who receive counseling seem to fare better academically in comparison to those who do not receive any intervention but who exhibit similar difficulties and characteristics. This effect is four times the 0.1 standard deviation effect size criterion for successful interventions suggested by Bloom et al (2006) and Schwartz, Hopkins, and Stiefel (2021). Academic support offers no benefits but does not harm either.…”
Section: Returns To Special Education Programs In Inclusive School Se...mentioning
confidence: 59%
“…3 Despite the increasing number of students with SEN and the push to implement inclusive education, evidence on how special education (SpEd) placements -and inclusive placements in particular -affect academic and labor market returns of students with SEN is scarce. Existing research shows inconclusive effects of SpEd on academic performance (Hanushek, Kain, and Rivkin, 2002;Lavy and Schlosser, 2005;Keslair, Maurin, and McNally, 2012;Schwartz, Hopkins, and Stiefel, 2021) and on educational attainment (Ballis and Heath, forthcoming). Since early interventions in children's school curricula have a profound impact on children's academic and lifelong prospects (see among others Cappelen et al, 2020;Heckman, Pinto, and Savelyev, 2013;Duncan and Magnuson, 2013;Chetty et al, 2011;Heckman et al, 2010), it is crucial to provide teachers, parents, psychologists and policy makers with insights on which SpEd programs are effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While at school, it is important to assess the development of academic skills, especially literacy and numeracy, social skills, such as relating to others, and daily living skills. Recent studies have shown that special education interventions can be effective in meeting the needs of children with learning or behavioral difficulties in order to help them develop academic skills [9,10], whereas Wilcox [11] reports on several studies which found that students in inclusive classrooms made less academic progress than those who received specialized interventions. In another review, Gilmour [5] reported on a study which found that a special education intervention was more effective than inclusive education in improving the mathematics skills of children with learning difficulties.…”
Section: Short-term Achievement Of Children With Learning or Behavioral Difficultiesmentioning
confidence: 99%
“…In three of these studies, the performance data collected from the students were disaggregated to display the performance of students with LD along with the performance of the whole group of students. The performance of students with LD was highlighted since this group of students has been shown to exhibit substantial skill deficits and to earn failing or barely passing grades in subject‐area courses (Fore et al., 2008; Hughes & Schumaker, 1991; Schwartz et al., 2021a; Warner et al., 1980). These studies and the results associated with each of the four Content Enhancement Routines are described below.…”
Section: Figurementioning
confidence: 99%